Optimization of the Siskeudes Application and Village Financial Management on Financial Performance Through SOP as an Intervening Variable in Alignment with SDG’s No. 1 - Endang Noer Anisah; Supardi Supardi; Hadiah Fitriah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study analyzes the influence of the optimization of the SISKEUDES application and village financial management on financial performance through Standard Operating Procedures (SOP) as an intervening variable, in line with SDG No. 1. Using a quantitative approach and saturated sampling technique, the study involved village officials in Candi District, Sidoarjo Regency. The data were analyzed using SEM-PLS with SmartPLS 4 software. The results show that the optimization of SISKEUDES and financial management significantly affect financial performance, with SOP acting as a partial mediator. These findings highlight the importance of SOP integration in enhancing village governance and sustainable financial performance.